POTENSI KONSORSIUM BAKTERI PEMACU PERTUMBUHAN SEBAGAI BAHAN AKTIF PUPUK ORGANIK HAYATI PADA TANAMAN JAGUNG - Yun Sondang; Khazy Anty; Ramond Siregar (Universitas Muhammadiyah Purwokerto, 2020)
The purpose of this research are to determine the potential of consortium of plant growth-promoting bacteria as an active ingredients of bio-organic fertilizers and to determine the effect of bio-organic fertilizers on growth and production of maize. The research was carried out at the Politeknik Pertanian Negeri Payakumbuh Experimental Field, Limapuluh Kota Regency, West Sumatra in March-July 2020. The research was starting with the manufacture of water hyacinth bio-organic fertilizer (POH) which inoculated with a consortium of bacteria from the genera Pseudomonas and Bacillus. POH observations were carried out on species, population size, and nutrient content of bio-organic fertilizers. The POH application research was using a factorial design in a randomized block design with treatment I at POH 40, 80, 120, 160 ml / l water and treatment II with frequency of 2, 3, 4 times giving POH. The variables observed were N, P, K nutrient content, plant dry weight, and dry maize seed production. The results of the POH study contained P. aeruginosa, B. subtilis, and B. cereus with a total population of 2,8,107–2,8,108, potentially as active ingredients for bio-organic fertilizers. POH water hyacinth can increase plant N, P, K nutrients, plant dry weight, and dry maize seed production. The optimal POH dose for all observed variables is 80 ml / l of water.